Value of novel sponge capsules combined with AI-based cell DNA detection in early esophageal cancer screening - XU Mengdi, GAO Feng, ZHU Jian, CHEN Lei, QIN Yumeng, HUANG Yue, TANG Yinping, SHA Jie (Zhenduanxue lilun yu shijian)
Objective To explore the value of novel sponge capsules combined with AI-based cell DNA detectio in early esophageal cancer screening. Methods From June 2021 to June 2022, subjects aged >40 years who were willing to undergo esophageal cancer screening were recruited. Firstly, the subjects underwent a novel sponge cell capsule examination to collect cell specimens. Then the cytological DNA index (DI) was assessed using artificial intelligence (AI). Subsequently, all subjects underwent endoscopy. The relationship between cytologic DI values and endoscopic findings was evaluated. Results A total of 1 369 participants were enrolled. There were 25 cases of esophageal lesions confirmed by endoscopy, including 15 cases of low-grade intraepithelial neoplasia, 1 case of high-grade intraepithelial neoplasia, and 9 cases of esophageal cancer. There were 1 344 cases in the normal esophagus group. DI was 2.154 ± 0.339 in the normal group and 2.832 ± 0.479 in the lesion group. The DI value of the esophageal lesion group was significantly higher than that of the normal esophageal group, and the difference was statistically significant. Logistic regression analysis showed that the odds ratio (OR) of DI values between the esophageal lesion group and the normal esophagus group = 0.04 (95% CI: 0.017-0.096). The sponge capsules combined with DI value diagnosed esophageal lesions with an area under the ROC curve of 0.914, an optimal critical value of 2.450, a specificity of 83.71%, a sensitivity of 88.00%, and an accuracy of 83.78%. Conclusions The novel sponge capsules DI test can be used for screening of early esophageal cancer, and this method should be promoted in clinical practice.